Germination of palm seeds under periods of rehydration - Ferreira, Kássia Barros [UNESP]; Souza, Antonio Maricélio Borges De [UNESP]; Muniz, Ana Carolina Corrêa [UNESP]; Pivetta, Kathia Fernandes Lopes [UNESP] (Sociedade Brasileira de Floricultura e Plantas Ornamentais, 2021)
Palm seeds are indicative of being recalcitrant species. Seeds germination for many species, is slow and uneven, even in favorable conditions, often due to the resistance of the woody endocarp that makes them impermeable to water. Most species also have the characteristic of not tolerating the drying process at low moisture levels, thus losing their viability. In view of these considerations, the objective was to evaluate the effect of different periods of rehydration on the germinative process of seeds of royal palm, dwarf palm and jeriva. Seeds were homogenized and immersed in water containing 3 times their volume, with daily replacement. The experimental design used was completely randomized, with 5 treatments (0, 3, 6, 9, and 12 days of rehydration), with 4 replications of 25 seeds. The seeds were placed in transparent “gerbox” plastic boxes containing medium vermiculite as substrate and placed in BOD with a photoperiod of 16-hour of light and their respective optimum temperatures for each species. The number of germinated seeds was counted every 2 days until germination stabilized. The variables analyzed were germination percentage, germination speed index (GSI), average germination time (AGT) and distribution of germination over the days. Rehydration for 3 days increased the germination rate of royal palm seeds. For dwarf and jeriva species, rehydration did not influence the analyzed variables. The GSI and AGT were negatively influenced by the rehydration periods for royal palm. Rehydration prolonged the peak of germination of the studied species.

As sementes de palmeiras apresentam indicativo de serem recalcitrantes e a germinação, para muitas espécies, é lenta e desigual, mesmo em condições favoráveis, muitas vezes devido à resistência do endocarpo lenhoso que os tornam impermeáveis a água. A maioria das espécies possui ainda a característica de não tolerar o processo de secagem a baixos teores de umidade, perdendo assim sua viabilidade. Tendo em vista essas considerações, objetivou-se avaliar o efeito de diferentes períodos de reidratação no processo germinativo de sementes de palmeira-real, tamareira anã, e jeriva. As sementes foram homogeneizadas e imersas em água contendo 3 vezes o volume das mesmas, com substituição diária. O delineamento experimental utilizado foi o inteiramente casualizado, com 5 tratamentos (0, 3, 6, 9 e 12 dias de reidratação), com 4 repetições de 25 sementes. As sementes foram colocadas em caixas de plástico tipo “gerbox” transparentes contendo como substrato vermiculita média e colocadas em BOD com fotoperíodo de 16 horas de luz e suas respectivas temperaturas ótimas para cada espécie. A contagem do número de sementes germinadas foi realizada a cada 2 dias até estabilização da germinação. As variáveis analisadas foram porcentagem de germinação, índice de velocidade de germinação (IVG), tempo médio de germinação (TMG) e distribuição da germinação ao longo dos dias. A reidratação por 3 dias aumentou a taxa de germinação de sementes de palmeira-real. Para as espécies tamareira anã e jeriva a reidratação não influenciou nas variáveis analisadas. O IVG e TMG foram influenciados negativamente pelos períodos de reidratação para palmeira-real. A reidratação prolongou o pico de germinação das espécies estudadas.
Germinação de sementes de palmeiras sob períodos de reidratação
Keywords: Phoenix roebelenii O’Brien; Roystonea regia (Kunth) O.F. Cook; Syagrus romanzoffiana Cham. Glassm.; Phoenix roebelenii O’Brien; Roystonea regia (Kunth) O.F. Cook; Syagrus romanzoffiana Cham. Glassm.